Law in the Golden Horde and oirat states of the middle ages. Part 1 - E. N. Badmaeva; E. U. Omakaeva; U. V. Ochirov (Nomadic Civilization: Historical Research, 2022)
The article discusses the most important sources of Mongolian and Oirat-Kalmyk medieval law – the Great Yasa of Genghis Khan and Iki Tsaajin Bichik of 1640, which played a significant role in the formation and development of the legal system of nomadic Mongolian peoples. These two legislative monuments, in combination with other sources of law, regulated the nomadic army, organized according to a military hierarchical principle, streamlined the system of economic culture and social organization of society, covered various branches of law – criminal, civil, spiritual (religious), family, inheritance also procedural (court procedure, issues of administrative management of a militarytype state). In the system of Mongolian law, a fairly common legal source was “zarlik” (labels) – decrees of the Great Khans of the empire and individual rulers of the states of Genghisides, granted, protection and other letters. In the framework of our scientific research, the goal was set, through an analysis of the “Great Yasa” of Genghis Khan and “Iki Tsaajin Bichik 1640”, various labels of medieval rulers of the Great Mongolian State, to show the features of the legal regulation of public relations in the Golden Horde, in particular, in Mongolian and Oirat nomadic state formations.